EFEKTIFITAS PENGATURAN PERJANJIAN BAGI HASIL TANAH PERTANIAN DENGAN BERLAKUNYA UNDANG-UNDANG NOMOR 2 TAHUN 1960 - Khonsa Rahayu, Alya Maya; Raharjo, Purwono Sungkowo (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2020)
This research was conducted to find out whether the implementation of agricultural land-sharing agreements are in accordance with laws and regulations and whether there are obstacles in the implementation of agricultural land-sharing agreements in Ngemplak District, Boyolali Regency. This type of research used by the author is empirical juridical research. The type of data used is secondary data. Data collection techniques used were interviews and literature study. This study uses qualitative data analysis techniques to group data obtained from research in the field, and is associated with theories, principles, and legal norms obtained from library studies. Based on the results of the study the authors found that in the implementation of the production sharing agreement in Ngemplak District, Boyolali Regency was not in accordance with Law Number 2 of 1960, it was caused by the community still using local customary law, namely an oral or unwritten agreement made on the basis of trust and agreement from both parties, both landowners and tenants. The timeframe for the production sharing is divided into 2 (two), namely determined and unspecified, it is still ongoing until now and the expiration of the production sharing agreement is based on the agreement of both parties. The obstacle in implementing Revenue Sharing according to the Revenue Sharing Law is the lack of community knowledge, even the village administrator does not know about the Production Sharing Agreement.